A Vision of the Days: Studies in Early Jewish History and Historiography : In Honor of Daniel R. Schwartz - Brody, Robert,; Hacham, Noah,; Henten, Jan Willem van,; Piotrkowski, Meron, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2024)
This collection of essays treats many aspects of ancient Jewish history and modern historiography in this area, with an emphasis on the history and literature of the Second Temple period and especially on the writings of Josephus. It is dedicated to Daniel R. Schwarz, and reflects his central academic interests. Additional essays deal with historical and ideological aspects of classical rabbinic literature, with archeological finds and with perceptions of the Jews and Judaism on the part of non-Jews in the Second Temple period and later. See Less